Employee Engagement Strengthening Model in the Creative Industry: Analyzing the Role of Self-Efficacy and Perceived Organization Support as Predictors - Indajang, Kevin; Siregar, Robert Tua; Grace, Ernest; Dharma, Edy; Sudirman, Acai (Valid: Jurnal Ilmiah, 2024)
This research aims to build a model for strengthening employee engagement in the creative industry by examining the role of self-efficacy and perceived organizational support as the main predictors. This research uses quantitative methods to survey employees in various creative industry sectors in Indonesia. The population in this study comprises creative sector industry workers, and the population size is unknown. In this research, researchers used a purposive sampling technique with a sample size of 130 employees. The data analysis method used is based on regression analysis using the IBM SPSS 23 program. The results of the data analysis conclude that self-efficacy and perceived organizational support have a positive and significant effect on employee engagement. The results of this research can provide theoretical and practical contributions to human resource management in the creative industries. These findings are expected to show that self-efficacy and perceived organizational support significantly influence employee engagement and can be a basis for companies to design more effective employee management strategies.